Peran Servant Leadership pada Organizational Citizenship Behavior dengan Mediasi Job Satisfaction - Nur Jannah, Dewi Karomatun; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Universitas Hayam Wuruk Perbanas, 2023)
This study aims to determine the effect of servant leadership and perceived organizational support on organizational citizenship behavior through job satisfaction of PERUMDAM Tirta Projotamansari Bantul Yogyakarta emplo-yees. This research is quantitative, and primary data in the form of filling out questionnaires were taken with a census technique on 55 respondents. The data were collected through a direct survey, and then, processed using multiple linear regression analysis using SPSS version 23 and sobel test using daniel soper calculator. The results showed that servant leadership has a significant positive effect on job satisfaction, job satisfaction has a significant positive effect on organizational citizenship behavior, and job satisfaction mediates the effect of servant leadership on organizational citizenship behavior. Companies can improve the implementation of servant leadership which is still low among employees so that it can strengthen employee job satisfaction and contribute to organizational citizenship behavior.